IDENTIFY FAQ KNOWLEDGE GAP IN IT HELPDESK USING KNOWLEDGE MAPPING CASE STUDY: HALOSIS BPS-STATISTICS - Suwiyanto, Viktor; Sensuse, Dana Indra (Kementerian Komunikasi dan Informatika R.I., 2020)
One important feature of IT HelpDesk, such as HaloSIS, is knowledge base. This feature disseminate knowledge about problem solving knowledge. This knowledge base goals were to assist service desk for giving fast solution to problem reported by user call and to facilitate learning about problem solving for new member of technical support team. To improve problem solving performance, technical support team can update or add this knowledge base with new problem solving knowledge. However, until this day this knowledge base was not updated. This can lead HaloSIS into tacit knowledge problem. This tacit knowledge remain in technical support head and not documented to knowledge base. To identify new knowledge that was not yet transferred to knowledge base, HaloSIS team need to identify knowledge gap that happen in HaloSIS knowledge base. There is a tool of knowledge management that can be used for identifying knowledge gap. This tool is knowledge mapping. Knowledge map can be used to representing the incompleteness of the current knowledge network that will enable to attain a sustainable future. This study propose knowledge map building from troubleshooting log in HaloSIS. This study build current knowledge map based on FAQ knowledge and merge it with knowledge found in troubleshooting log. The methodology to build knowledge map was the 6-step method from Kim's research. The data analysis method used is qualitative data analysis method using thematic analysis.Â From this knowledge map this study found 15 new know-how knowledge and recomendation to update 7 know-how knowledge. However, there are some limitations of this study which only maps the online presence system. For future research, it is necessary to build a knowledge map for all services in HaloSIS comprehensively to maintain, renewal, and seeking for knowledge.